Pengaruh Kualitas Layanan Elektronik, Kualitas Makanan, Persepsi Manfaat Dan Kemudahan Terhadap Kepuasan Konsumen Dan Niat Pembelian Ulang Pada Pizza Hut Delivery Di Surabaya - yanuar danu prasetyo; Tatik Suryani (Jurnal Manajerial, 2023)
Background – How to satisfy and attract customer intention is very crucial for supporting business performance. Now days, not only the quality of foods and product benefits but also the technology online supporting are very important. Pizza Hut one of a big restaurant have implemented online applications for improve it’s services. So, it’s very important to examine the impact of their online service attributes on Consumer Satisfaction and Repurchase Intentions. Aim – This study aims to examine the effect of Electronic Service Quality, Food Quality, Perceived Benefits, Perceived of Easiness on Customer Satisfaction and Intention to Repurchase Pizza Hut product in Surabaya. Design / Methodology / Approach –Type of this research is quantitative with survey method by distributed questionnaires. 150 respondents involved in this research which selected by purposive sampling with criteria such as consumer often buy product by using online services and lives in Surabaya. Structural Equation Modelling Smart-PLS program was used for analyzing data. Findings – Electronic Service Quality, Food Quality, Perceived Benefits and Perceived Ease of Use effect significantly toward Customer Satisfaction. Electronic Service Quality and Customer Satisfaction effect significantly on Repurchase Intention. Food Quality, Perceived Benefits and Perceived Ease to Use have no significant effect on Repurchase Intention. Conclusion - 9 hypotheses were proposed to see the relationship between variables 3 of which were rejected, namely Food Quality, Perceived Benefits, Perceived Convenience had no significant effect on Repurchase Intentions Research implication – Customer satisfaction is paramount and it can be driven through keeping Electronic Service Quality, Food Quality, Perceived Benefits and Perceived Ease of Use Limitations – this research was not analyzed further this effect of attributes of online application implementation the consumers based on digital literacy